Real-world evidence study finds no new-onset diabetes or drug-related hyperglycemia in Pompe disease patients treated with avalglucosidase alfa - Alexandra Dumitriu; Ann Lucas; Raffaella Colzani (Molecular Genetics and Metabolism Reports, 2024)
Avalglucosidase alfa therapy for Pompe disease is diluted in dextrose 5% solution in water (D5W) for infusion, which raises questions about the potential for hyperglycemia or worsening diabetes. Using United States insurance claims data, we assessed the impact of biweekly infusions on hyperglycemia, new-onset diabetes mellitus, insulin resistance, and prediabetes in patients with Pompe disease. After starting avalglucosidase alfa treatment, 1 of 26 patients had one claim for hyperglycemia, which was attributed to acute pancreatitis.